(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The current article discusses the main features of literary images and typological analysis in the poetry of William Blake. Additionally, author emphasize symbolical meaning of mystic images in the works of William Blake including “Songs of Innocence and Experience”. The mastery of William Blake is closely connected to religious and mystical philosophy of Middle Ages Literature which reveals real rebellion to injustice in Middle England.